Analisis Sistem Drainase di Wilayah Kota Depok - Kerlima Hutagaol; Agnes Intan Permatasari; Betman Dasuha Purba; Dizzy Putrafakhmi; Sri Hartanto (SENTRI: Jurnal Riset Ilmiah, 2025)
In general, the condition of drainage systems in various cities across Indonesia is facing a wide range of problems. An effective drainage system plays a crucial role in preventing floods and waterlogging, especially in densely populated urban areas such as Depok City. With the rapid pace of urbanization, the drainage infrastructure in Depok is confronted with multiple challenges, both technical and environmental in nature. This article examines the current state of the drainage system in Depok by utilizing reliable data and documenting real-life occurrences observed in the field. Through an in-depth analysis of rainfall data, the physical condition of drainage channels, and several flooding incidents that have occurred in recent years, this paper aims to provide a comprehensive overview of the situation. It also seeks to offer practical and strategic recommendations to improve drainage management in the area, thereby supporting better urban planning, disaster mitigation, and sustainable infrastructure development in the long term.